The Roommate Problem - Is More Stable Than You Think - Pierre-André Chiappori; Alfred Galichon; Bernard Salanié (Center for Economic Studies and ifo Institute (CESifo), 2014)
Stable matchings may fail to exist in the roommate matching problem, both when utility is transferable and when it is not. We show that when utility is transferable, the existence of a stable matching is restored when there is an even number of individuals of indistinguishable characteristics and tastes (types). As a consequence, when the number of individuals of any given type is large enough there always exist "quasi-stable" matchings: a stable matching can be restored with minimal policy intervention. Our results build on an analogy with an associated bipartite problem; it follows that the tools crafted in empirical studies of the marriage problem can easily be adapted to the roommate problem.
Keywords: C78; J12; 330